(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Consumer purchasing decisions affect sales, thus there is a need for promotion through digital marketing. The purpose of this study is to ascertain how Puteri Kentucky multipurpose flour product purchasing decisions are affected in part and simultaneously by digital marketing, product quality, and pricing. 90 samples were used in this study, and the population consisted of all consumers who had purchased Puteri Kentucky Flour Products. We were using a purposive sampling methodology and distributing questionnaires as a data collecting tool. With the aid of the Windows SPSS application, multiple linear regression analysis is the test approach performed. The findings of this research are 1) Digital marketing partially influences consumer decisions to purchase Puteri Kentucky multifunctional seasoning flour goods positively and significantly. 2) Product quality partially influences consumer decisions to buy Puteri Kentucky multipurpose seasoning flour in a favorable and important way. 3) Price influences purchases of PuteriKentucky multifunctional seasoning flour goods in a favorable and significant way. 4) The Puteri Kentucky multifunctional seasoning flour product has a simultaneous positive and strong influence of digital marketing, product quality, and pricing on purchasing decisions.